Are Women Really Different? Comparison of Men and Women in a Sample of Forensic Psychiatric Inpatients - Streb, Judith; Lutz, Maximilian; Dudeck, Manuela; Klein, Verena; Maaß, Christina; Fritz, Michael; Franke, Irina (Frontiers in Psychiatry, 2022)
Background: Women in detention remain a widely understudied group. Although the number of studies in women in prison has grown in the past decade, research on female forensic psychiatric inpatients has not increased, and women are in the minority in forensic psychiatry not only as patients but also as examinees. Consequently, most treatment manuals and risk assessments were developed in male samples and apply to male offenders. However, the same treatment and risk assessment rationale can be applied in male and female mentally ill offenders only if evidence shows that no relevant sex differences exist. Aims: The aim of the present study was to examine a sample of male and female forensic psychiatric inpatients with substance use disorders and to compare the sociodemographic, legal, and clinical characteristics between the sexes. Methods: The sample included 115 male and 61 female patients. All patients were in mandatory inpatient forensic psychiatry treatment according to section 64 of the German penal code. Results: We found no significant differences between men and women in terms of educational status and vocational training. However, women were more often single and less likely to be employed full time, and they reported adverse childhood experiences more often than men. Regarding clinical variables, women appeared to be less likely to have a substance use disorder due to alcohol use and had more previous psychiatric treatments than men. Male patients were significantly younger on first conviction and detention, had more criminal records and served longer total penalties than female patients. Furthermore, men committed more violent crimes and women, more narcotics-related crimes. Conclusions: The study identified sex-specific differences in forensic psychiatric patients that should be considered in the context of forensic therapy.